2023
DOI: 10.7554/elife.85416
|View full text |Cite
|
Sign up to set email alerts
|

Single cell preparations of Mycobacterium tuberculosis damage the mycobacterial envelope and disrupt macrophage interactions

Abstract: For decades, investigators have studied the interaction of Mycobacterium tuberculosis (Mtb) with macrophages, which serve as a major cellular niche for the bacilli. Because Mtb are prone to aggregation, investigators rely on varied methods to disaggregate the bacteria for these studies. Here, we examined the impact of routinely used preparation methods on bacterial cell envelope integrity, macrophage inflammatory responses, and intracellular Mtb survival. We found that both gentle sonication and filtering dama… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that proteins present on the outer surface of cells may get stripped off due to the presence of detergents. 36 By growing cells in the absence of tyloxapol, we aimed to retain capsular components and the natural abundance of the surface-exposed proteins. 37 While cell surface accessibility of mycobacterial OMPs has been previously shown by flow cytometry, direct microscopic evidence of their surface localization is lacking.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that proteins present on the outer surface of cells may get stripped off due to the presence of detergents. 36 By growing cells in the absence of tyloxapol, we aimed to retain capsular components and the natural abundance of the surface-exposed proteins. 37 While cell surface accessibility of mycobacterial OMPs has been previously shown by flow cytometry, direct microscopic evidence of their surface localization is lacking.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Cell surface accessibility of outer membrane proteins is what distinguishes them from inner membrane or periplasmic proteins and was assessed by probing the accessibility of the C-terminal FLAG-tag with Alexa Fluor 488-tagged antibody without permeabilization. Previous studies have shown that proteins present on the outer surface of cells may get stripped off due to the presence of detergents . By growing cells in the absence of tyloxapol, we aimed to retain capsular components and the natural abundance of the surface-exposed proteins .…”
Section: Resultsmentioning
confidence: 99%
“…Cell surface accessibility of outer membrane proteins is what distinguishes them from inner membrane or periplasmic proteins and was assessed by probing the accessibility of the C-terminal FLAG-tag with Alexa Fluor 488-tagged antibody. Previous studies have shown that proteins present on the outer surface of cells may get stripped off due to presence of detergents (62). By growing cells in the absence of tyloxapol, we aimed to retain capsular components and the natural abundance of the surface-exposed proteins (63).…”
Section: Resultsmentioning
confidence: 99%
“…Although several methods are used to minimize this problem (e.g., use of detergents in the culture media and physical methods for disaggregation), these can influence macrophage responses and intracellular bacterial survival and should therefore be reported. 46 When reporting, researchers should describe the species of bacterial strain used, including strain number or reference with details on strain type used, and the bacterial identity confirmation by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectroscopy or genotyping under the Methods section. If using a clinical isolate, all available information should be included, including method of isolation and media used for maintenance.…”
Section: Bacterial Characterizationmentioning
confidence: 99%
“…An important consideration when working with M. tuberculosis is the lipid-rich nature of the mycobacterial cell wall; this makes cultures very prone to aggregation, which can impact the accuracy and reproducibility of bacterial numbers delivered during intracellular infections. Although several methods are used to minimize this problem (e.g., use of detergents in the culture media and physical methods for disaggregation), these can influence macrophage responses and intracellular bacterial survival and should therefore be reported …”
Section: Experimental Considerations and Reporting Recommendations Fo...mentioning
confidence: 99%